THE EFFECT OF LEADERSHIP STYLE AND COMPENSATION ON ORGANIZATIONAL COMMITMENT OF BABINSA IN JAKARTA - Dicky Hida Syahchari; Lifany Husnul Kurnia (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2018)
This study investigates the conceptualization of the leadership style and compensation within organizational commitment of Babinsa in Jakarta as  well  as examining  the   leadership style and compensation  on  organizational commitment by  previous  researchers. This study use qualitative method by  reviewing  and  integrates  previous  studies  to  point  to  the  significance  of  the   leadership style and compensation towards organizational commitment of Babinsa specifically in  Jakarta. This  study proposes  a  research  framework  to  investigate  the  relationship  of  leadership style and compensation  on organizational commitment of Babinsa in Jakarta. The study is  particularly  useful for  practitioners  by  identifying  advantages  of  suitable  organizational commitment of Babinsa in Jakarta.